2012
DOI: 10.1210/jc.2012-2298
|View full text |Cite
|
Sign up to set email alerts
|

Use of PET/CT with Cosyntropin Stimulation to Identify and Localize Adrenal Rest Tissue following Adrenalectomy in a Woman with Congenital Adrenal Hyperplasia

Abstract: Patients with CAH after an adrenalectomy may experience recurrent hyperandrogenism due to adrenal rest tissue. 18F-FDG PET/CT with cosyntropin stimulation accurately identified adrenal rest tissue not visualized with conventional imaging, allowing for successful surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The FDG PET/CT is performed after ACTH stimulation which leads to increased visibility of FDG uptake in adrenal rests [157,158].…”
Section: Adrenocortical Adenomamentioning
confidence: 99%
“…The FDG PET/CT is performed after ACTH stimulation which leads to increased visibility of FDG uptake in adrenal rests [157,158].…”
Section: Adrenocortical Adenomamentioning
confidence: 99%
“…Lila et al [24 ]reported the use of 18 F-FDG PET/CT in the detection of ectopic adrenal rests in a patient who developed Nelson's syndrome after bilateral adrenalectomy for Cushing's disease. Crocker et al [25] described a similar case of a young adult female patient with CAH with hyperandrogenism after bilateral adrenalectomy. They detected adrenal rests in both ovaries by using 18 F-FDG PET/CT after cosyntropin stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The most radical treatment is the surgical removal of both adrenal glands. This approach must be carefully discussed as it can induce the development of TARTs in men and less frequently retroperitoneal adrenal rest tumors in women (73,74). Chemical adrenalectomy may be obtained using mitotane, an adrenolytic agent for which the mechanisms of action remain poorly understood.…”
Section: Treatment Of Classic Cah Adultsmentioning
confidence: 99%